2011
DOI: 10.1590/s1516-14392011005000041
|View full text |Cite
|
Sign up to set email alerts
|

Study of epoxy/CNT nanocomposites prepared via dispersion in the hardener

Abstract: In this study, carboxylated (SWCNT-c) and pristine (SWCNT) single-walled carbon nanotubes were randomly dispersed in a hardener prior to mixing it with an epoxy resin. The influence of several parameters on the dispersion process were investigated. The produced samples were characterized by infrared spectroscopy, differential scanning calorimetry, dilatometry, dynamic mechanical analysis, scanning electron microscopy and mechanical testing (tensile, flexural and microhardness). The results obtained with the na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…Figure shows a DSC curve of a cured DGEBA/PDMS‐a/TETA specimen, prepared by the mixture of PDMS‐a/TETA 50/50 (m/m) with an equimolar amount of DGEBA, indicating a glass transition temperature (Tg) of 49.8°C. This Tg is well below the reported value for the same DGEBA/TETA system used in this work, around 107°C, pointing out the role of PDMS‐a in the toughening of DGEBA/mPDMS‐a/mTETA systems after self healing.…”
Section: Resultssupporting
confidence: 41%
“…Figure shows a DSC curve of a cured DGEBA/PDMS‐a/TETA specimen, prepared by the mixture of PDMS‐a/TETA 50/50 (m/m) with an equimolar amount of DGEBA, indicating a glass transition temperature (Tg) of 49.8°C. This Tg is well below the reported value for the same DGEBA/TETA system used in this work, around 107°C, pointing out the role of PDMS‐a in the toughening of DGEBA/mPDMS‐a/mTETA systems after self healing.…”
Section: Resultssupporting
confidence: 41%
“…5 (b), one can note the pull-out occurring in one of the high concentration regions. In another study of the same research group in a similar system (epoxy/CNTs), there is strong evidence of pullout found by SEM [36]. It can also be seen in Fig.…”
Section: Crack Bridging E Pull-outmentioning
confidence: 56%
“…These properties show a trend toward higher modulus and strength and a trend toward lower strain for higher MWCNT contents. Although it can be debated that the variations are in the expected range, these effects are influenced by two other factors that reduce the aspect ratio of the nanotubes or influence the presence of the CNT on the curing degree of the thermoset resin. This correlation has been previously reported .…”
Section: Resultsmentioning
confidence: 99%